Side effects: Why Left and Right Matter. - Sobieski, Sonya (Psychology Today)
Human brains are cross-wired: The right half controls the left side of the body, and the left half controls the right. There are some tasks, however, that one side of the brain—and its attendant, opposing side of the body—carry out better. Details of which sides control which actions are presented.